ANALISIS SOSIOLINGUISTIK PERSPEKTIF GENDER TERHADAP NASKAH DRAMA “SAMPEK ENGTAY” KARYA ANDRI WICAKSONO DAN DAN M. AHMAD JALIDU - Dewi hartati Dewi Hartati; Ika Septiana; Senowarsito (STKIP Subang, 2026)
This descriptive qualitative study aims to dissect the sociolinguistic aspects of gender in a drama script set within the early 20th-century Javanese-Chinese community. Through content analysis and critical discourse analysis methods, lingual units comprising the characters' dialogues, dictions, and metaphors are classified objectively to unravel the asymmetric power relations between masculine (report-talk) and feminine (rapport-talk) speech styles. The results show that within a patriarchal social structure, male characters utilize directive language, pejorative vocabulary, and domestication discourse as instruments of dominance to restrict women's mobility and silence their verbal authority. This condition forces women to internalize the hegemony that oppresses them. However, crucial findings prove that female subjects are not always passive. Through the character of Engtay, a dynamic practice of linguistic cross-dressing occurs in the form of identity disguise and the mastery of linguistic capital. Engtay cleverly adopts a formal-authoritative colonial legal register, engages in code-switching, manipulates institutional hygiene discourse through pseudo-theological arguments, and applies an off-record (indirect) communication strategy in the form of riddle codes. The data validity checking technique uses theoretical triangulation of feminist sociolinguistics and gender performativity to ensure the accuracy of the hermeneutic data. In conclusion, linguistic power is not a biological given but a social construction, thereby granting women full sociolinguistic flexibility to perform subversion, deconstruct patriarchal dominance, and negotiate gender equality in the public sphere.